Molecular Diagnostics in the Times of Surveillance for Candida auris - Milena Kordalewska; David S. Perlin (Journal of Fungi, 2019)
Recently, global health professionals have been significantly challenged by the emergence of Candida auris and its propensity to colonize human skin, persist in the healthcare environment, and cause healthcare-associated outbreaks. Additionally, C. auris isolates are often characterized by elevated minimal inhibitory concentration (MIC) values for antifungal drugs. Thus, rapid detection and accurate identification of C. auris together with an assessment of potential antifungal drug resistance has become essential for effective patient management, and infection prevention and control in healthcare facilities. Surprisingly, almost all of the commonly available diagnostic tools rely on recovery (growth) of yeast colonies from collected samples, which delays the diagnostic result by several days or longer. To circumvent these issues, molecular-based DNA amplification assays have been developed to identify C. auris DNA directly from patient samples. Moreover, allele discriminating detection probes can be used to rapidly assess validated mechanisms of echinocandin and azole resistance.